Geometry and topology of groups - Otera, Daniele Ettore (Lietuvos matematikos rinkinys, 2013)
This short note is a slightly expanded version of the talk given by the author at the 54th LMD Conference, devoted to present a very informal and brief introduction to the main ideas of the asymptotic geometry of groups.